Culture and Cognition: Essays in Honor of Peter Damerow - Jürgen Renn (ed.); Matthias Schemmel (ed.) (Edition Open Access, 2021)
Peter Damerow (1939–2011) was a visionary scholar of rare versatility. A key figure in the foundation and early development of the Max Planck Institute for the History of Science, he contributed to fields as wide-ranging as pedagogy, mathematics, philosophy, psychology, Near Eastern studies, as well as the history of knowledge and science. Through his work and his dynamic personality, he shaped the careers of many scholars worldwide. He was a paragon of the engaged scientist, having great sensitivity for political and social concerns and a perceptiveness that also shaped his scholarship. The present volume attempts to capture the vivacity of his ever-curious mind. It comprises contributions by some of his closest companions, colleagues, and friends, most of which were presented at a workshop held in Peter’s honor at the Max Planck Institute for the History of Science in Berlin in December 19–20, 2013. The contributions are organized in four parts, the first three of which cover some of the areas of Peter’s interests: the origins of writing and mathematics; the history of knowledge and science; and societal concerns and the role of information technologies for the humanities. The last part offers a glimpse at his life and also presents the scope of his scholarship with a bibliography of his writings.